Synthesis And Characterization Of Lanthanide-Benzoato Complexes - Ooi, Ping Howe (2011)
Sixteen complexes and three single crystals of lanthanide-benzoato were synthesized with normal refluxing and solvothermal method. The structures of the three crystals were characterized using single crystal X-ray crystallography.[Nd2(C7H5O2)6(C12H8N2)2],[Eu2(C7H5O2)6(C12H8N2)2